Traditional games as a strategy in the teaching-learning process - Salcedo Quiroz, Wilmer Moisés; Goez Truco, Shirle; Guarín Suárez, Samir; Aponte Rivera, Adriana (Rastros Rostros, 2022)
The game as a basic element of pedagogy and educational methodologies brings important benefits to both development and learning, considering that it contributes to improving the experience that children live. In this way, the main objective is to determine the role of traditional games as a strategy in the teaching-learning process of the students of Basic Primary Education of the Educational Institution La Ventura, of San Benito Abad Sucre. The methodology to be used is based on a quantitative approach with a descriptive - exploratory scope and a non-experimental cross-sectional design, the sample will be made up of primary school teachers, and as an instrument for collecting information, a survey will be built focused on the teachers of the institution. The results show that an almost insignificant proportion of teachers make use of playful strategies, as well as perceive that the school does not have adequate spaces for recreation. In this way, it is concluded that traditional games are a resource that can be of great help to promote the acquisition of knowledge in the classroom and that their use should be increased.